2017
DOI: 10.1002/anie.201700286
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Steam Reforming Strategy to Delaminate Layered Carbon Nitride Semiconductors for Photoredox Catalysis

Abstract: The delamination of layered crystals that produces single or few-layered nanosheets while enabling exotic physical and chemical properties, particularly for semiconductor functions in optoelectronic applications, remains a challenge. Here, we report a facile and green approach to prepare few-layered polymeric carbon nitride (PCN) semiconductors by a one-step carbon/nitrogen steam reforming reaction. Bulky PCN, obtained from typical precursors including urea, melamine, dicyandiamide, and thiourea, are exfoliate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
178
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 403 publications
(186 citation statements)
references
References 51 publications
6
178
0
Order By: Relevance
“…For the XRD pattern of NiCo 2 O 4 NNs@g‐C 3 N 4 /CC, it could be clearly found that in addition to the diffraction peaks originated from CC and NiCo 2 O 4 , a diffraction peak positioned at 27.8° can be observed, which corresponding to the (002) crystal plane of g‐C 3 N 4 (JCPDS file No. 87–15),, indicating that the as‐prepared sample is made up of CC, NiCo 2 O 4 and g‐C 3 N 4 . FTIR spectra of the as‐synthesized NiCo 2 O 4 NNs@g‐C 3 N 4 also confirmed the successful coating of g‐C 3 N 4 film.…”
Section: Resultsmentioning
confidence: 99%
“…For the XRD pattern of NiCo 2 O 4 NNs@g‐C 3 N 4 /CC, it could be clearly found that in addition to the diffraction peaks originated from CC and NiCo 2 O 4 , a diffraction peak positioned at 27.8° can be observed, which corresponding to the (002) crystal plane of g‐C 3 N 4 (JCPDS file No. 87–15),, indicating that the as‐prepared sample is made up of CC, NiCo 2 O 4 and g‐C 3 N 4 . FTIR spectra of the as‐synthesized NiCo 2 O 4 NNs@g‐C 3 N 4 also confirmed the successful coating of g‐C 3 N 4 film.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, photocatalysis has harnessed the use of solar energy in a strategy to overcome environmental problems; as a result, the development of resourceful and highly efficient photocatalysts is crucial for achieving its practical application . In the past few years, an organic skeleton material, carbon nitride, has drawn extensive attention .…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic diffraction peaks are located at 27.5°corresponding to (002) interface ,. This characteristic peak indicates that graphite carbonitridation, has been successfully synthesized. The three stronger peaks in CNC correspond to (300), (113) and (122) interfaces in the standard Cu 3 P card, and their corresponding angles are 44.93, 45.97 and 47.07°, respectively.…”
Section: Resultsmentioning
confidence: 93%